The Christ Child on Fire: Southwell's Mighty Babe. (12th September 2013) - Kenney, Theresa M.
Abstract : The image of the Proleptic Passion – the Christ Child bearing the wounds of the crucifixion—figures in Robert Southwell's representation of time and immediacy, that is, his temporal rhetoric. This image was ceasing to be conventional in his lifetime because of Reformation attitudes toward the Eucharist and toward the mimetic possibilities of poetry itself; thus, Southwell's use of it harkens back to medieval traditions. In the "Burning Babe" and "New Heaven, New Warre, " the governing images collapse temporal sequences in Christ's life, merging his birth and death and making his sacrifice present to the meditating poet, imitating divine eternity, with the Child as nexus of eternity and time. Southwell's understanding of the unitive power of both the Incarnation and sacrifice informs the first poem more than does the emblem tradition. Medieval lyrics, patristic writings on the Incarnation that link the Eucharist and the Nativity and depict the newborn Christ as a warrior, and Flemish depictions of the Nativity no doubt familiar to Southwell lie behind both poems. In the multivalent image of the mighty Babe, Southwell is able to portray the Christ Child as both suffering redeemer and powerful judge at the end of time. (T. M. K.)